DEBT AND RISK DISCLOSURE ROLE ON FIRM VALUE IN INDONESIA - Triaryati, Nyoman; Indrawati, Ayu Desi; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025DO - 10.24843/EEB.2025.v14.i01.p11, 2025)
This study examines and explains how risk disclosure supports debt's role in growth opportunities, profitability, and real assets' effect on firm value. The limited role of risk disclosure in previous studies and changes in market participants' interest in small mid-cap firms in IDX motivated it. The conditional process model analysis method used moderated mediation analysis based on the research framework. The test was conducted on small mid-cap firms on the IDX. The results show that debt and risk disclosure only have a role as a signal in growth opportunities and real assets' effects, not profitability. This signal determines the perceptions and expectations of market participants towards the firm. Complementary mediation and omitted variables emerge in the analysis results, showing that other variables are suspected as intermediary variables other than debt. More voluntary risk disclosure is an effective way to ensure the positive perception of the market participant. As the firm can balance the benefits of debt and risk, it could be a signal to anticipate the risks that market participants expect, and the desired firm value will be achieved.